Why do we still cling to spirometry for assessing small airway function? - Trinkmann, Frederik; Watz, Henrik; Herth, Felix (The European respiratory journal, 2020)
Extract - With great interest we read the article by Arshad et al. [1] and the accompanying editorial [2] in the March 2020 issue of the European Respiratory Journal. We fully agree that early detection and small airway function are both of utmost importance for the management of obstructive lung disease. However, we have some methodological concerns in this context. These should be discussed as certain imitations of the important work at hand. - Tweetable abstract ERSpublications - click to tweetSmall airway function comprises heterogenous interactions between ventilation, diffusion, perfusion and inflammation that cannot be covered by spirometry https://bit.ly/2LiyQ5E
Gesehen am 23.09.2020